In-Process Inventories and Multiproduct Production Systems: A Comment. - Feltham, Gerald A. (The Accounting Review, 1973)
The article comments on the analysis of two researchers on in-process inventories and multiproduct production systems. In a previous article, the author assumed that the in-process inventories are constant from period to period. He explains that the researchers' analysis did not define what the level of activity represents in this context. They also implicitly assumed that the units of in-process inventory are complete with regard to the internal inputs used in producing them. In an analysis designed to consider in-process inventories, such assumption is considered odd.